Pemanfaatan Limbah Sekam Menjadi Produk Arang Sekam untuk Meningkatkan Nilai Jual di Desa Gunturmekar, Kabupaten Sumedang - Dinda Emmy Gusti Sofhia; Wiwin Nurhasanah; Jono Mintarto Munandar (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Agricultural waste can be in the form of unused waste material and waste material from processing. Gunturmekar Village, Sumedang Regency is a village that mostly earns a living as a farmer. Many people, especially rice processors, do not make optimal use of rice husks. Therefore, this husk processing activity intends to utilize the husk into something of high value so that it can be reused for agriculture including being used as a planting medium. The target of this activity is rice processors with the aim of increasing the value of rice husks, increasing the income of rice processors and improving the community's economy, especially rice processors. The results of this activity are the creation of new products, namely husk charcoal used for soil softening, compost-making material, bokashi fertilizer, planting media, and nursery media. The benefits of husk charcoal stimulate the growth of microorganisms, regulate soil pH, retain moisture, and suppress pathogenic microbes. Based on the evaluation, the whole husk processing activities went well. This activity can increase the added value of the husk product. However, there are several obstacles in its processing, namely the tools used in making husk charcoal are still very simple and produce enough smoke so that it can cause air pollution that can disturb the surrounding environment. Therefore, the tools used to make husk charcoal need to be improved. In addition, this husk processing activity has only been carried out in two hamlets, so it is necessary to introduce this husk processing to people who are in other hamlets in Gunturmekar Village. Keywords: Charcoal husk, Gunturmekar Village, rice